Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) dengan Pemodelan Green Product dan Green Advertising terhadap Keputusan Pembelian di Kabupaten Purworejo Provinsi Jawa Tengah - Budiyanto Budiyanto; Mahendra Galih Prasaja (SEGMEN Jurnal Manajemen dan Bisnis, 2020)
The increasingly business competition is now fully realized by micro small and medium enterprises (MSME). Business actors continue to strive to innovation strategies on the products they offer to consumers, so that their products have high competitiveness and remain capable of being the choice of consumers. A new phenomenon in the marketing world is the concept of green marketing. Green marketing campaign program in Indonesia is shown from the development of environmentally friendly products (green products). Marketers carry out promotion of these green products through the most effective form of promotion by using green advertising. This study aims to examine whether green product and green advertising partially have a positive and significant effect on purchasing decisions on product consumers.Population this study all MSME product consumers in Purworejo and had seen MSME product advertisements, while the sample used was 120 respondents with a purposive sampling technique. Data collection in this study used a questionnaire filled out by those who met the research sample requirements. The questionnaire was tested and met the validity and reliability requirements. Data analysis uses multiple regression and hypothesis testing. The results of multiple regression analysis and hypothesis testing indicate that the green product variable has a positive effect and significant green advertising has a positive and not significant effect on purchasing decisions partially. Keywords: green marketing, green advertising, green product and MSME